Cómo incide la afectividad en el desarrollo escolar en los niños de 3 a 4 años de edad del centro de educación inicial “Niño Jesús” de la ciudad de Loja, periodo lectivo 2014 – 2015. Lineamientos alternativos - Ochoa Medina, Martha Isabel (2016)
This research refers to: CÓMO INCIDE LA AFECTIVIDAD EN EL DESARROLLO ESCOLAR EN LOS NIÑOS DE 3 A 4 AÑOS DE EDAD DEL CENTRO DE EDUCACIÓN INICIAL “NIÑO JESÚS” DE LA CIUDAD DE LOJA, PERÍODO LECTIVO 2014 – 2015. LINEAMIENTOS ALTERNATIVOS, the same that was developed according to Reglamente Academic Board of the National University of Loja. How central issue was raised: How affective impact on school development in children of 3-4 years old Early Education Center "Baby Jesus" in the city of Loja, during the 2014-2015 school? The overall objective: To analyze how this affects the emotions in the school development in children 3-4 years old Early Education Center "Baby Jesus" in the city of Loja, school 2014-2015. The methods used for the development of this research were: scientific, inductive, deductive, descriptive and statistical model that enabled them to reach efficiently the proposed research. The techniques and instruments used were: the survey to parents of children aged 3 and 4 years old was applied to obtain information on issues related to emotions, test eBee León Gross was applied children aged 4 years to assess the emotional development. According to the results it is concluded that: 62% of parents say they worry about getting the educational development of children, 36% said they frequently do, while 2% mentioned that sometimes, denoting there is a constant concern of parents for school development of children, maintaining a good relationship with their children emotional partner. According to test results Ebee León Gross to assess the emotional development of children, 89% have a satisfactory effective development, which requires attention to the relations of parents with their children, while 11 % have a satisfying emotional development, denoting relations of affection between parents and their children are very good or excellent.